(untitled) (Journal of actual problems of jurisprudence, 2023)
This article analyzes one of the theoretical problems of modern insurance law. The complex of norms regulating insurance relations with their development acquires a new status. Insurance legislation is no longer an institution of financial law, but a complex legal formation. This is evidenced by a separate subject of legal regulation - insurance relations, methods of legal regulation - containing more dispositive norms, principles of legal regulation, distinguishing features of insurance law from other branches of law. All these issues are considered by the author in the article below. The conclusions made by the author are based on a comprehensive study of the essence and characteristics of insurance relations, as well as modern insurance legislation and state policy in the regulation of insurance activities in the Republic of Kazakhstan. The practical significance of this article lies in the possibility of using theoretical results in further research in the field of insurance law, development and improvement of norms and insurance legislation of the Republic of Kazakhstan. It should be noted that questions related to the definition of the place of insurance law in the system of law have always been the subject of study by many scientists in developing insurance relations in a closed economy, and in the new market relations already in the independent states. Keywords: insurance law, insurance activity, insurance legislation, insurance relations.